2011
DOI: 10.1097/qmh.0b013e3182134af0
|View full text |Cite
|
Sign up to set email alerts
|

Excess Health Care Service Utilization and Costs Associated With Underrecognition of Psychiatric Comorbidity in a Medical/Surgical Inpatient Setting

Abstract: Psychiatric comorbidity is common among chronically medically ill populations and the presence of psychiatric conditions tends to be associated with increased costs and excess utilization of general medical services. The purpose of this pilot investigation was to determine whether differences in nonpsychiatric inpatient hospitalization frequency, duration, and costs existed between patients receiving outpatient psychiatric treatment and patients without identified psychiatric problems. Length of stay and cost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…Finally, Borckardt et al(2011) reported a positive association between outpatient psychiatric visits and hospital admissions in a retrospective study of a single hospital population. 22 The prevalence of SMI in our study population (6%) was low compared to that of other studies, in which the reported prevalence of SMI ranges from 8.2% – 34%. 8, 15, 16, 23, 24 This may be due to our dependence upon discharge diagnosis codes to verify mental illness diagnoses.…”
Section: Discussioncontrasting
confidence: 73%
“…Finally, Borckardt et al(2011) reported a positive association between outpatient psychiatric visits and hospital admissions in a retrospective study of a single hospital population. 22 The prevalence of SMI in our study population (6%) was low compared to that of other studies, in which the reported prevalence of SMI ranges from 8.2% – 34%. 8, 15, 16, 23, 24 This may be due to our dependence upon discharge diagnosis codes to verify mental illness diagnoses.…”
Section: Discussioncontrasting
confidence: 73%
“…This relationship was described in ten (19%) studies [ 8 , 9 , 44 , 45 , 51 , 61 65 ]; of these, nine (90%) revealed that medical-psychiatric comorbidities related to increased rehospitalizations. Seven (70%) studies found a significant increase [[ 8 , 9 , 44 , 51 , 61 , 62 , 64 ], two (20%) noted a non-significant increase [ 45 , 65 ] and one (10%) found neither an increase nor decrease [ 63 ]. A meta-analysis was not executed since the data could not be used in a meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Saravay and colleagues [ 38 ] found that those with post-stroke depression averaged twice as many readmissions and spent twice as many days re-hospitalized over a 4-year period. Similarly, Borckardt and colleagues [ 39 ] found that psychiatrically involved outpatients had higher average readmissions (mean = 1.6) compared to non-psychiatric outpatients (mean = 1.34) over one year. However, both studies only report unadjusted readmissions and do not utilize regression techniques to account for the effects of other patient characteristics on hospitalizations.…”
Section: Discussionmentioning
confidence: 87%